Money and the coming world order - Cleveland, Harold van B.; Kindleberger, Charles P.; Lehrman, Lewis E.; Calleo, David P. ([New York] : New York University Press, 1976)
This book examines the postwar world political economy and its evolution, as well as the role of policy makers in the monetary system after the World war and during the Cold war period.
Includes bibliographical references.
usc 16/08/2018
Loans
Keywords: International finance; Economic history